Acquiring pragmatics : social and cognitive perspectives - Zufferey, Sandrine (Routledge Taylor & Francis Group, 2015)
During the past decades, pragmatics has been a rapidly growing field of study, and considerable paradigm shifts have occurred. From the study of socially determined rulesgoverning the production of speech acts, pragmatics has now also become part of the cognitive sciences, and aims at understanding how listeners bridge the gap between the under-determined linguistic meaning of utterances and the full-blown speaker's meaning. Acquiring Pragmatics is a comprehensive synthesis of state-of-the-art research on the acquisition of pragmatics, covering both social and cognitive dimensions. The text introduces advanced undergraduate and graduate students, as well as scholars from neighboring fields of study to the current topics of research in theoretical pragmatics, the issues they raise for language acquisition research and the new experimental designs that have been developed to address them empirically